Ultrasound of the Gastrointestinal Tract - Maconi, Giovanni.; Maconi, Giovanni.; Bianchi Porro, Gabriele.; Bianchi Porro, Gabriele. (Diagnostic Imaging, 2014)
This is the second, updated and extended edition of a well-received book that offers a comprehensive overview of ultrasonographic imaging of acute and chronic gastrointestinal diseases, including acute abdomen, appendicitis, diverticulitis, inflammatory bowel diseases, neoplasms and masses, infections, malabsorption syndromes, and rare conditions. The value of ultrasound in each disorder is clearly explained and illustrated, and limitations identified. Information is also provided on recent technical developments and ultrasound applications that are likely to become of increasing importance, such as functional and 3D ultrasound, contrast agents and intraoperative ultrasound, elastography, and transperineal ultrasound. The authors are all distinguished experts in the topics they address. Ultrasound of the Gastrointestinal Tract will be a helpful guide in daily practice not only for radiologists but also for gastroenterologists, abdominal surgeons, pediatricians, and oncologists.